Approximated analytical solution to an Ebola optimal control problem. Issue 5 (1st November 2016) - Hincapié-Palacio, Doracelly; Ospina, Juan; Torres, Delfim F. M.
ABSTRACT: An analytical expression for the optimal control of an Ebola problem is obtained. The analytical solution is found as a first-order approximation to the Pontryagin Maximum Principle via the Euler–Lagrange equation. An implementation of the method is given using the computer algebra systemMaple . Our analytical solutions confirm the results recently reported in the literature using numerical methods.